Outcome of Topical Dapsone 5% Versus Topical Clindamycin 1% in Treatment of Mild to Moderate Acne Vulgaris: Topical Dapsone 5% Versus Topical Clindamycin 1% in Treatment of Acne Vulgaris - Iftikhar, Muhammad Bilal; Saqib, Zareen; Bashir, Bushra (Pakistan Journal of Health Sciences, 2025)
Acne vulgaris is a common inflammatory skin disorder, and increasing resistance to conventional topical antibiotics has highlighted the need for alternative therapies such as dispone. Objective: To compare the outcome of topical dapsone 5% gel versus topical clindamycin 1% gel in the treatment of mild to moderate acne vulgaris. Methods: A Randomized Controlled trial was conducted in the Dermatology Department of Allama Iqbal Memorial Teaching Hospital, Sialkot, from February 2025 to July 2025. A total of 131 patients aged between 18 and 60 years, diagnosed with mild to moderate acne vulgaris based on the Global Acne Grading System (GAGS), were consecutively enrolled. Participants were randomly allocated into two groups (Group A: clindamycin 1% gel twice daily, Group B: dapsone 5% gel once daily). Both regimens were continued for 12 weeks. Mean difference and percentage reduction in GAGS scores, along with adverse events, were noted as outcomes. Results: Both groups had similar baseline characteristics without significant differences (p>0.05). At 12 weeks, mean GAGS scores were significantly lower in the clindamycin group (9.27 ± 2.95) than in the dapsone group (10.57 ± 4.33; p=0.047). Percent reduction in GAGS score was also significantly greater with clindamycin (44.97 ± 14.37) compared to dapsone (38.72 ± 18.52; p=0.033). No adverse events occurred in the Clindamycin 1% gel group, while 5 (7.6%) in the Dapsone 5% gel group reported oily skin, pruritus, or irritation. Conclusions: Clindamycin 1% gel demonstrated superior efficacy and tolerability compared to Dapsone 5% gel in reducing acne severity over 12 weeks.